2002
DOI: 10.1006/mthe.2002.0696
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression and HIV-1 Inhibition of Chimeric tRNALys3-Ribozymes under Dual U6 snRNA and tRNA Promoters

Abstract: We previously demonstrated that chimeric tRNA(Lys3)-ribozymes targeting the primer binding site of HIV produced virions with reduced infectivity. To further enhance the anti-HIV efficiency of these ribozymes by increasing their level of transcription, we designed several tRNA(Lys3) promoter variants and compared their expression levels from the internal tRNA(Lys3) promoters and also from an exogenous human U6 snRNA promoter. The dual U6/tRNA promoter constructs gave rise to much higher levels of expression tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Indeed, a tRNA promoter is located within the tRNA scaffold (Chang, et al, 2002; Schramm and Hernandez, 2002). To test this, we expressed tBroccoli without using the U6 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a tRNA promoter is located within the tRNA scaffold (Chang, et al, 2002; Schramm and Hernandez, 2002). To test this, we expressed tBroccoli without using the U6 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is not surprising since the mutated ribozyme can still bind to its target mRNA, and thus may elicit antisense-like inhibitory effects on protein production. In addition, it is conceivable that the short doublestranded regions in the mutant ribozyme±target RNA complex may attract intracellular double-strand-speci®c RNase activity, resulting in decreased target mRNAs as observed here for some clones (27). Also, small interfering RNA (siRNA)-like effects may potentially contribute to such decreases, although the strict sequence and length requirements for siRNAs make this less likely (28,29).…”
Section: Discussionmentioning
confidence: 96%
“…37 While no toxicity has been observed in this study, the moderate effect reported emphasizes the need to find more inhibitory molecules for use in gene therapy. Approaches that have been described to identify new Rz candidates include the use of (i) RNA Polymerase III (Pol III) promoters to achieve higher levels of expression, 38,39 (ii) cellular screens to identify optimal target sites, 18,19 (iii) chimeric Rzs to enhance anti-viral effects, 18,27,40,41 and (iv) alternative motifs such as modified RNase P and HDV Rzs. 7,16 In this study, we screened SOFA-HDV-Rzs, expressed from the RNA Pol III H1 promoter, targeting the 5′UTR and Gag coding sequence of HIV-1 RNA for effects on viral production.…”
Section: Discussionmentioning
confidence: 99%